The development of a wireless LCP-based intracranial pressure sensor for traumatic brain injury patients - Preedipat Sattayasoonthorn; Jackrit Suthakorn; Sorayouth Chamnanvej M.D (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Raised intracranial pressure (ICP) in traumatic brain injury (TBI) patients can lead to death. ICP measurement is required to monitor the condition of a patient and to inform TBI treatment. This work presents a new wireless liquid crystal polymer (LCP) based ICP sensor. The sensor is designed with the purpose of measuring ICP and wirelessly transmitting the signal to an external monitoring unit. The sensor is minimally invasive and biocompatible due to the mechanical design and the use of LCP. A prototype sensor and associated wireless module are fabricated and tested to demonstrate the functionality and performance of the wireless LCP-based ICP sensor. Experimental results show that the wireless LCP-based ICP sensor can operate in the pressure range of 0 - 60.12 mmHg. Based on repeated measurements, the sensitivity of the sensor is found to be 25.62 µVmmHg-1, with a standard deviation of ± 1.16 µVmmHg-1. This work represents a significant step towards achieving a wireless, implantable, minimally invasive ICP monitoring strategy for TBI patients.